O papel da religiosidade e do suporte social na depressão : resultados do estudo epidemiológico São Paulo Megacity Mental Health Survey - Paiva, Maria Cristina Alochio de (2014)
The objective of this study is to estimate the role of religiosity and social support in depression and describe religiosity and perceived physical and mental health and its relationship with sociodemographic variables in the adult population in the São Paulo Metropolitan Area, Brazil. Data were analyzed from a subsample (n = 2,942) of the São Paulo Megacity Mental Health Survey, cross-sectional study of population-based evaluating mental disorders in a probability sample of the general population aged 18 years or more, using the version of the Composite International Diagnostic Interview from the World Health Organization. They were analized dimensions of religiosity, perceived health, social support from friends, search for health services and intensity of symptoms of depression, were being used proportions and standard error for descriptive analysis and logistic regression for the associations. The results show high religiosity of the population, and the religion as a very important thing in the daily lives of the interviewees and their frequent use when they have problems. The perception of mental health is better than the physical one with the worsening of the last with age in both genders. Individual religious practices were positively associated with a decrease in the perception of poor mental health in the sample and the importance of religion in life was positively associated with perceived poor physical health among men No association was observed between religiosity and depression, or between social support from friends and depression. People with organizational religiosity and depression in the last 12 months seek more medical services.